Trade-offs in plant defense against pests and pathogens and strategies for crop health management - CHAKRABORTY, B.N. (Indian Phytopathology, 2013)
Plants are constantly being challenged by aspiring pathogens, but disease is rare. Why? Broadly, there are three reasons for pathogen failure. Either (a) the plant is unable to support the niche requirements of a potential pathogen and is thus a non host; or (b) the plant possesses preformed structural barriers or toxic compounds that confine successful infections to specialized pathogen species; or (c) upon recognition of the attacking pathogen defense mechanisms are elaborated and the invasion remains localized. All three types of interaction are said to be incompatible, but only the latter resistance mechanism depends on induced responses. Successful pathogen invasion and disease development occurs, if the preformed plant defenses are inappropriate, the plant does not detect the pathogen or the activated defense responses are ineffective. Advances made in the formulation of concepts and techniques of modern, quantitative cell biology in recent years have paved the way for a basic understanding of molecular events in developing resistance during host-pathogen interactions. In spite of this what still eludes our grasp is the answer to the high degree of specificity of the host-pathogen combinations observed in nature. In fact, if one considers the multitude of microorganisms to which plants are being continuously exposed in nature, the significance of specificity becomes more apparent. Until and unless the mechanisms whereby a host and pathogen ‘recognize’ the potential for establishing a compatible or incompatible relationship are identified, and the devices whereby specificity for that relationship is established, it cannot be claimed that a full understanding of host-pathogen interactions has been achieved.